Role of MicroRNAs in the Regulation of Subcutaneous White Adipose Tissue in Individuals With Obesity and Without Type 2 Diabetes - Brovkina, O.; Nikitin, A.; Khodyrev, D.; Shestakova, E.; Sklyanik, I.; Panevina, A.; Stafeev, Iurii; Menshikov, M.; Kobelyatskaya, A.; Yurasov, A.; Fedenko, V.; Yashkov, Yu; et al. (Frontiers in Endocrinology, 2019)
Obesity is a high-risk factor for such comorbidities as cardiovascular disease, several types of cancer, and type 2 diabetes; however not all obese people have such complications. Approximately 20% of obese patients are metabolically healthy. This study focused on differences between obese individuals with and without type 2 diabetes (T2D+ and T2D-, respectively) on the transcriptome level. Subjects included were 35 obese T2D- patients and 35 obese T2D+ patients with the same body mass index. The study was based on the transcription analysis of mRNA and microRNAs (miRs) by RNAseq. In the first step, we performed RNAseq of miRs, in the second step, we analyzed only those mRNA, which appeared targets for significant miRs from the first step. All RNAseq results were validated by qPCR. There were seven miRs significantly dysregulated with adjusted p-value <0.1, which were confirmed by qPCR. Five among them: miR-204-5p, miR125b-5p, miR-125a-5p, miR320a, miR-99b - were upregulated in obese T2D+ patients, while only two miRs, miR-23b-3p and miR197-3p, were increased in obese T2D- patients. These seven miRs target two groups of genes: matrix metalloproteinases and TGFβ signal pathway genes. The main difference between obese T2D+ and T2D- patients was in adipogenesis and fibrosis regulation by matrix metalloproteinases and SMAD4-RUNX2 signal cascade. Based on the data about transcription profiles of both groups, we suggested that the process of fibrosis in obese T2D+ patients is more pronounced than in obese T2D- patients.